2001
DOI: 10.1017/s1357729800058124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maize and citrus-pulp supplementation of urea-treated wheat straw on intake and productivity in female lambs

Abstract: Two experiments with lambs given food indoors and individually penned were designed to study the effects of different levels of ground maize and citrus pulp as supplements of a diet based on urea-treated straw (5 kg urea per 100 kg straw) offered ad libitum over a period of 16 weeks (experiment 1) or 10 weeks (experiment 2). The voluntary intake, live-weight gain (LWG), organic matter digestibility (OMD), urinary allantoin-nitrogen (UAN) excretion and acetate clearance rate were measured. The lambs were blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
10
3
Order By: Relevance
“…Clearance of glucose has previously been shown to become less efficient during the first few weeks of a calf's life (Bunting et al, 2000). The acetate clearance test was first used by Pugh and Scarisbrick (1952) and has been used since to characterize effects of diet on acetate supply to growing lambs (Cronjé et al, 1991;Fonseca et al, 2001;Chakeredza et al, 2002). To our knowledge, the BHB clearance test has not been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Clearance of glucose has previously been shown to become less efficient during the first few weeks of a calf's life (Bunting et al, 2000). The acetate clearance test was first used by Pugh and Scarisbrick (1952) and has been used since to characterize effects of diet on acetate supply to growing lambs (Cronjé et al, 1991;Fonseca et al, 2001;Chakeredza et al, 2002). To our knowledge, the BHB clearance test has not been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Higher DMI in lambs fed 33 and 66% of OP compared to control group might be due to increase in rumen out flow rate. Fonseca et al (2001) reported that increasing the amount of OP in diets of fattening lambs led to increase in rumen out flow rate. Also, in agreement with our results, Ammerman et al (1963) observed that the inclusion of OP in the diets increased DMI and stated that rations containing OP are more palatable than those containing corn.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, it is thought that volatile fatty acids, which play an active role in shaping milk yield, are not sufficiently released in the rumen and sufficient resources cannot be sent to the liver to raise blood glucose levels. The low level of volatile fatty acid production in the rumen may cause by the orange pulp's increasing the ruminal flow rate (Fonseca et al, 2001), the suppressing of the rumen microorganisms by enteric oils in the pulp (Barrios-Urdanetat et al, 2003;Nam et al, 2006) or the rapid digestion of sugar and causing a sudden drop in pH and disrupting rumen dynamics.…”
Section: Performance Findingsmentioning
confidence: 99%
“…Even though orange pulp has similar amounts of energy (about 2980 kcal/kg DM) with cereals (Bampidis and Robinson, 2006), there are studies reporting that performance decreases by affecting rumen dynamics negatively or neutrally. Dried citrus pulp increases ruminal fluid flow and reduces dry matter digestion in the rumen (Fonseca et al, 2001), the use of dried citrus pulp instead of barley suppresses rumen bacteria (Barrios-Urdanetat et al, 2003), and citrus essential oils also have antimicrobial effects (Nam et al, 2006). Due to these reasons, it can be thought that a decrease in milk yield and a deterioration in feed efficiency rate occur, since enough volatile fatty acids will not be released in the rumen.…”
Section: Performance Findingsmentioning
confidence: 99%